Dampak Pengembangan Pantai Kilo Lima Pada Masyarakat Lokal di Kota Luwuk Kabupaten Banggai - Anda Prasetyo Ery; Dharma Kuba; Ariesta (Politeknik Pariwisata Makassar, Indonesia, 2020)
Tourism development often does not pay attention to the preservation of natural resources and local culture which are also affected by tourism development and considers that the tourism industry is an industry whose existence is interrelated. This research is descriptive research in the form of written or oral words from people and observable behavior and to be able to better identify the variables to be examined in relation to them and aims to present a structured, factual, and accurate description of the facts -fact and the relationship between the variables to be studied. From the results of the study there are positive and negative impacts that arise. Both environmental, socio-cultural, and economic impacts on local communities who are the main actors who feel the impact of tourism development. The community has felt the positive impact provided by the tourism sector. Although there are still negative impacts that are also felt